Kearifan Lokal dan Pengembangan Identitas untuk Promosi Wisata Budaya di Kabupaten Banyumas - Triana Ahdiati (Jurnal Pariwisata Terapan, 2020)
The development of local identity reflecting the local wisdom in the tourism development aims at maximizing the local values in developing the area.  This research-based paper describes the local wisdom and the development of local identity to promote cultural tourisme in Banyumas.  By using a qualitative method and a case study as its approach, the research reveals that the tourism development in the Banyumas regency has not focused on the development of its local identity yet.  Cablaka as the local identity of the Banyumas society has not become the way of life.  In this case, it has not absorbed into every sector of the Banyumas people’ lives, including the tourism sector.  The local wisdom in the tourism development is important for a society–including the Banyumas society–to get a better regional income.  It means the tourism develoment through implementating the local wisdom is able to improve the life condition of a society better than before.  So, the tourism development–especially promoting the cultural tourism–in the Banyumas regency does need to develop the local identity through its local values.